Squamosamide Derivative FLZ Protects Pancreatic β-Cells from Glucotoxicity by Stimulating Akt-FOXO1 Pathway - Xiangchen Kong; Longmei Zhang; Xianxin Hua; Xiaosong Ma (Journal of Diabetes Research)
Chronic hyperglycemia increases apoptosis and reduces glucose-stimulated insulin secretion. Although protective agents have been searched extensively, none has been found so far. Here we tested FLZ, a synthetic derivative of squamosamide from a Chinese herb, as a potential candidate for antiglucotoxicity in INS-1E cells and mouse islets. Chronic culture of β-cells in 30 mM glucose caused progressive reduction of cell viability, accompanied with increased apoptosis and reduced insulin secretion. These effects on apoptosis and insulin were reversed by FLZ in a dose-dependent manner. FLZ treatment also increased forkhead box O1 protein phosphorylation and reduced its nuclear location. On the contrary, FLZ increased pancreatic and duodenal homeobox-1 expression and its nuclear localization, an effect mediated by increased p-Akt. Consistently, Akt selective inhibitor MK-2206 completely abolished antiglucotoxicity effect of FLZ. Furthermore, FLZ treatment increased cytosolic ATP/ADP ratio. Taken together, our results suggest that FLZ could be a potential therapeutic agent to treat the hyperglycemia-induced β-cell failure.